How Do Work Discipline, Compensation And Competence Influence Employee Productivity? - Wenny Arimah Pramesti; Siti Nur Azizah (JPS (Jurnal Perbankan Syariah), 2023)
Islamic banks require employee productivity, where employee productivity indicates the continuity of bank business productivity. This research aims to analyze the extent to which work discipline, compensation, and competence impact employee productivity. The research uses a quantitative approach with primary data in the form of a questionnaire. The data analysis technique uses partial least squares structural equation statistical modelling, and data processing is carried out using SmartPLS 3.0 software. The population of this study was all employees of Bank Muamalat, Yogyakarta’s main branch office (MBO), totalling 65 people. The research sample consisted of 65 employees selected using a saturated sampling procedure. The research results show a positive and statistically significant impact between work discipline and employee productivity. However, the results of this study did not identify a significant impact between compensation and competency on employee productivity. The results of this research can complement existing theories and can be used as material for consideration and information for Bank Muamalat Yogyakarta’s MBO in making decisions to increase employee productivity.